2021
DOI: 10.1186/s12889-021-10492-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between participation in, intensity of, and time spent on leisure time physical activity and risk of inflammatory bowel disease among older adults (PA-IBD): a prospective cohort study

Abstract: Background Inflammatory bowel diseases (IBDs) are diseases of the immune system that share some genetic and lifestyle-related predisposing factors. Increasing incidences have been reported in all age groups. Based on experimental studies suggesting a role of physical activity on intestinal inflammation, this study aimed to investigate the association between leisure time physical activity and the risk of IBD in older adults. Methods The study is a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
2
4
0
1
Order By: Relevance
“…These findings are in line with the result of a review of metaanalyses recently published, that demonstrated a protective effect of physical activity regarding the development of CD [32]. On the other hand, a Danish prospective cohort study reported no association between physical activity and risk of IBD [33]. A possible explanation for this discrepancy to our result is, that the Danish study did not investigate the association between timing in life of physical activity and risk of IBD.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are in line with the result of a review of metaanalyses recently published, that demonstrated a protective effect of physical activity regarding the development of CD [32]. On the other hand, a Danish prospective cohort study reported no association between physical activity and risk of IBD [33]. A possible explanation for this discrepancy to our result is, that the Danish study did not investigate the association between timing in life of physical activity and risk of IBD.…”
Section: Discussionsupporting
confidence: 82%
“…These findings align with previous meta-analyses indicating a protective effect of physical activity against CD development [3]. However, it is important to note the nuanced nature of these associations as demonstrated by conflicting evidence from other studies such as a Danish prospective cohort study that reported no significant association between physical activity and IBD risk [4]. The protective effect of regular physical activity against IBD onset can be attri­buted to its impact on various aspects of the immune system and inflammatory processes.…”
Section: Knowledge Transfer Of Merve Guney-coskun (Istanbul) and Sara...supporting
confidence: 88%
“…Within the same adult population cohort, a recent prospective study proposed that a healthy lifestyle, including adequate PA, might have prevented 61% of CD and 42% of UC cases 26 . Contrary, a Danish prospective cohort study showed no relationship between IBD risk and the degree of PA amongst elderly individuals 27 …”
Section: Discussionmentioning
confidence: 96%
“… 26 Contrary, a Danish prospective cohort study showed no relationship between IBD risk and the degree of PA amongst elderly individuals. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation